Return and onward migration, attachment and travel of New Zealand migrants to Australia - Poot, Jacques; Sanderson, Lynda (Penerbit Universiti Kebangsaan Malaysia, 2007)
This article is concerned with the internarional mobility of New Zealanders who migrate to Australia. We study New Zealand migrants arriving in Australia between I August 1999 and 31 July 2002. We track all subsequent moves of these migrants out of and back into Australia, up to July 2005. Using hazard models, we find that the removal of labour market-related social security eligibility by Australia for New Zealand migrants increased the probability of remigration from Australia among those who had intended to settle pemanently. Competing risk models suggested no difference between the impacts of the policy changes on onward or return moves. Settlers arriving afer the policy changes were more likely to migrate again, to have lower attachment to Australia, and to make more trips away.